Human-home-canal: The guideline for the souvenir product design to reflect the cultural way and community life of Chumchon Ban Khrua - Chaidirek, Pornnaree (Edelweiss Applied Science and Technology, 2025)
This study aims to explore and present the cultural identity of Chumchon Ban Khrua, a historic and culturally rich community, and to design souvenir products that reflect its unique identity. The research objectives include collecting and analyzing data on the history, architecture, local wisdom, and cultural capital of Chumchon Ban Khrua; developing design guidelines for souvenirs; and creating prototypes of tourist souvenir products. Utilizing both quantitative and qualitative methods, data were collected through literature reviews, surveys, interviews with local residents, and collaboration with experts using the Ethnographic Delphi Futures Research (EDFR) technique. The research also incorporated questionnaires to gather insights on tourist preferences. The design process synthesized historical and cultural data into five collections of prototypes, which were refined through expert and focus group evaluations. One final collection, consisting of seven souvenir items, was selected and further developed into virtual prototypes. Key findings include the identification of cultural identities such as Cham Muslim traditions, silk weaving, Pattani Malay architecture, and natural dyeing techniques. The study also presented cultural and sustainable design concepts, emphasizing storytelling, functionality, and the integration of recycled materials. Prototypes were evaluated for their aesthetic appeal, market feasibility, and alignment with community values, contributing to cultural conservation, pride, and economic development through tourism. The research outcomes included exhibition dissemination, academic publications, and practical guidelines for cultural product development, offering a model for similar community projects.